Transradial versus transfemoral approach for cerebral angiography: A prospective comparison - Ziliang Wang; Jinchao Xia; Wei Wang; Gangqin Xu; Jianjun Gu; Yongfeng Wang; Tianxiao Li (Journal of Interventional Medicine, 2019)
Objectives: To evaluate the feasibility, efficiency, and safety of the transradial approach (TRA) for cerebral angiography versus the transfemoral approach (TFA) in patients. Methods: In this trial, 2314 patients underwent cerebral angiography, with 1085 patients undergoing the procedure via radial access and 1229 via transfemoral access. The arterial puncture time, operation success rate, oppression time on puncture points, local vascular complication incidence (including bleeding, hematoma, and pseudoaneurysm), deep venous thrombosis of lower limbs (DVT), and bradycardia/hypotension were observed and compared between the two groups. Results: Of the patients who underwent cerebral angiography via radial access, the procedure was successful in 1070 patients; compared with 1219 patients with transfemoral access, there was no significant difference (P > 0.05) in the success rate or the arterial puncture time. Radial access patients were less likely to present with oppression time on puncture points, local vascular complications, DVT, and bradycardia/hypotension compared with femoral access patients. Conclusions: For patients undergoing cerebral angiography, radial and femoral approaches are both safe and effective. However, the lower rate of local vascular complications may be a reason to use the radial approach. Keywords: Cerebral angiography, Transradial approach, Transfemoral approach, Intervention